Analysing Social Entrepreneurship Innovation Through Sustainability Compass - Dien Yudithadewi; Sigit Tri Hartanto; Bonifasius Santiko Parikesit; Rio Zakarias Widyandaru (Future Science, 2022)
This study aims to examine how social entrepreneurship that supports women's empowerment, can answer social issues, as well as fulfilling Sustainable Development Goals (SDGs) no.5; gender equality and empower all women and girls. The social enterprise is Pagar Dewa Waste Bank, which is operated under the auspices of the Village-Owned Enterprise in Pagar Dewa Village, Lubai Ulu Sub District, Muara Enim District, South Sumatra Province. The research design used a qualitative method, and the data collection process was carried out through in-depth interviews with relevant stakeholders. The respondents include beneficiaries, government, communities, and the company itself. Researchers also searched for secondary data through observations and literature reviews from digital media, books, and journals to enrich the study. Field findings were analyzed by referring to the four dimensions of sustainability, which is initiated by Herman Daly and further developed by Alan Atkisson, namely the Sustainability Compass. It elaborates sustainability through compass terms: N (North) for Nature, E (East) for Economy, W (West) for Wellbeing, and S (South) for Society. The result of the study indicates that innovation is an important element for the success of social entrepreneurship. In this case, innovation can change people's behavior in a positive direction. The program is successfully capable to answer social issues regarding Sustainability Compass (nature, economy, society, and wellbeing), as well as fulfilling SDGs no.5 (gender equality and empowering all women and girls). The Sustainability Compass is effective to review the impact of the program comprehensively.